Электронная коммерция в Украине : проблемы правового регулирования - Гаряева, Анна Михайловна; Примшиц, Юлия Игоревна; Мелешкова, Юлия Сергеевна (НТУ "ХПИ", 2013)
The article high lights the problems of legal regulation of electronic documents and e-commerce in Ukraine. Digital signature as one of the instruments regulating relations in the field of electronic commerce is considered.
Keywords: подпись электронно-цифровая; онлайн-торговля; законодательство; Интернет